Misi sebagai Rencana Allah: Kesatuan Injil Matius dan Kisah Para Rasul dalam Sejarah Keselamatan - Stefani, Stefani; Stevanus, Kalis (Sekolah Tinggi Teologi Tawangmangu, 2025)
This study aims to demonstrate the theological unity between the evangelistic mission referred to as the Great Commission in Matthew 28:18–20 and the practice of evangelism in the book of Acts as an integral part of the realization of God's mission of salvation. The Great Commission is not a human initiative, but a divine command originating from the authority of Christ and carried out under the guidance of the Holy Spirit. The methods used are narrative-theological and literature study. The results of the study are to show the integral continuity of the narrative of Matthew 28:18–20 serves as the theological foundation of the church's mission, while the Acts of the Apostles shows the concrete realization of the mandate in evangelistic actions. Thus, the two texts demonstrate the unity of the narrative of Matthew and the Acts of the Apostles so that the church today has a complete theological basis in carrying out its mission and the Holy Spirit as its main agent or as a link between the Christological proclamation (Matthew) and the ecclesiological realization (Acts of the Apostles) which confirms the mission as an integral part of the work of the Trinity. AbstrakPenelitian ini bertujuan untuk menunjukkan kesatuan teologis antara misi penginjilan yang disebut Amanat Agung dalam Matius 28:18–20 dan praktik penginjilan dalam kitab Kisah Para Rasul sebagai bagian integral dari realisasi misi keselamatan Allah. Amanat Agung bukanlah inisiatif manusia, melainkan perintah ilahi yang bersumber dari otoritas Kristus dan dilaksanakan di bawah tuntunan Roh Kudus. Metode yang digunakan adalah naratif-teologis dan studi kepustakaan. Hasil penelitian adalah menunjukkan kesinambungan integral narasi Matius 28:18–20 berfungsi sebagai landasan teologis misi gereja, sedangkan Kisah Para Rasul memperlihatkan realisasi konkret mandat tersebut dalam tindakan penginjilan. Dengan demikian, kedua teks tersebut memerlihatkan kesatuan narasi Matius dan Kisah Para Rasul agar gereja masa kini memiliki dasar teologis yang utuh dalam melaksanakan misi dan Roh Kudus sebagai agen utamanya atau sebagai penghubung antara proklamasi Kristologis (Matius) dan realisasi ekklesiologis (Kisah Para Rasul) yang menegaskan misi sebagai bagian integral dari karya Trinitas.